Plasma focus ion beam fluence and flux - For various gases - Lee, S. (AIP Publishing, 2013)
A recent paper derived benchmarks for deuteron beam fluence and flux in a plasma focus (PF) [S. Lee and S. H. Saw, Phys. Plasmas 19, 112703 (2012)]. In the present work we start from first principles, derive the flux equation of the ion beam of any gas; link to the Lee Model code and hence compute the ion beam properties of the PF. The results show that, for a given PF, the fluence, flux, ion number and ion current decrease from the lightest to the heaviest gas except for trend-breaking higher values for Ar fluence and flux. The energy fluence, energy flux, power flow, and damage factors are relatively constant from H 2 to N 2 but increase for Ne, Ar, Kr and Xe due to radiative cooling and collapse effects. This paper provides much needed benchmark reference values and scaling trends for ion beams of a PF operated in any gas.